Diagnostic evaluation of river discharge into the Arctic Ocean and its impact on oceanic volume transports - Susanna Winkelbauer (Department of Meteorology and Geophysics, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Michael Mayer (Department of Meteorology and Geophysics, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Vanessa Seitner (Department of Meteorology and Geophysics, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Ervin Zsoter (European Centre for Medium-Range Weather Forecasts); Hao Zuo (European Centre for Medium-Range Weather Forecasts); Leopold Haimberger (Department of Meteorology and Geophysics, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna) (Hydrology and Earth System Sciences, 2022)
The abstract is available here: https://uscholar.univie.ac.at/o:1653685 The abstract is available here: https://uscholar.univie.ac.at/o:1653685